Numerical study on ratcheting performance of heavy haul rail flash-butt welds in curved tracks. (October 2022) - Wu, Yiping; Lun Pun, Chung; Su, Hang; Huang, Pu; Welsby, Darrien; Mutton, Peter; Yan, Wenyi
Highlights: The FaStrip algorithm is modified to estimate elastic-plastic traction distribution. Softened zones of rail welds experience the highest ratcheting strain rate. Ratcheting strain rates in the sampled 2000 m radius curved track are higher than those in the sampled tangent track. The RCF initiation location is highly dependent on the magnitude and pattern of traction distribution. Abstract: Ratcheting at the rail heads due to cyclic rolling contact stresses is often observed in heavy haul railways, especially when there are large steering forces developed in low-radius curves. Additionally, ratcheting behaviour can be exacerbated when associated with material strength loss in the heat affected zones of rail welds. However, the numerical evaluation of this failure mode requires a sophisticated representation of elastic–plastic contact pressures and traction distributions, which, to the best of the authors' knowledge, cannot be directly measured by any existing tools. In this paper, in order to accurately evaluate the ratcheting performance at rail welds in curved tracks, attempts were conducted to modify the FaStrip algorithm to analytically estimate the traction distributions based on contact pressures and creepages obtained from static finite element analysis and multi-body dynamic simulations, respectively. Cyclic rolling contact was then simulated by repeatedly applying contact pressure and traction on the rail surface consisting of both the rail weld and the parent rail regions. The weld region was divided into 23 sub-zones in the rolling direction to represent the material inhomogeneity within the heat affected zones. Cases on a 2000 m radius curved track and a tangent track were studied for comparison. It was found that the ratcheting strain rate in curved tracks can be significantly elevated due to the higher magnitude of traction, and the location of the elements with the highest ratcheting strain rate was dependent on the traction distribution patterns. The proposed method provides a general tool for predicting rolling contact fatigue initiation life and location, which will benefit the maintenance efficiency of heavy haul rail welds in curved track.